Islam and the West : a conversation with Jacques Derrida - Derrida, Jacques (Religion and postmodernism., 2008)
In the spring of 2003, Jacques Derrida sat down for a public debate in Paris with Algerian intellectual Mustapha Chérif. The eminent philosopher arrived at the event directly from the hospital where he had just been diagnosed with pancreatic cancer, the illness that would take his life just over a year later. That he still participated in the exchange testifies to the magnitude of the subject at hand: the increasingly distressed relationship between Islam and the West, and the questions of freedom, justice, and democracy that surround it. As Chérif relates in this account of their dialogue, th.